Identifying Academic Demands That Occasion Problem Behaviors for Students With Behavioral Disorders: Illustrations at the Elementary School Level. (January 2015) - Hagan-Burke, Shanna; Gilmour, Maria Wynne; Gerow, Stephanie; Crowder, William Clay
In two independent experiments, we (a) examined aspects of academic demands associated with the problem behaviors of two elementary students with behavioral disorders and (b) investigated the effects of academic interventions to decrease problem behaviors and increase task engagement. Preliminary functional behavior assessment data suggested each student participant's problem behaviors functioned to escape/avoid academic demands, and experimental structural analyses performed in naturalistic settings confirmed relations between their problem behaviors and specific features of academic tasks. Antecedent-based interventions were developed for each student and separate single-case alternating treatment experiments indicated functional relations between the academic interventions and appropriate task engagement. Findings support the use of structural analyses to inform academic planning and improve the behaviors of students who exhibit escape-maintained problem behaviors associated with academic tasks.